2021
DOI: 10.1080/26395916.2021.1957021
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of non-timber forest products to people in mountain ecosystems and impacts of recent climate change

Abstract: Non-timber forest products (NTFPs) are some of nature's most important contributions to people in mountain regions and their provision is increasingly affected by climate change. Here, we identify the types of NTFPs and their contributions to people in the mountain communities of the Upper Madi Watershed of Nepal and describe how these are being impacted by climate change. We used a field-based household survey supplemented with key informant interviews to collect quantitative and qualitative data on their use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Distribution in Nepal: Jiri (Janakpur), Dagchu (Solukhumbu), Kathmandu (Sugi 1993), Kaski (Gurung et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution in Nepal: Jiri (Janakpur), Dagchu (Solukhumbu), Kathmandu (Sugi 1993), Kaski (Gurung et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Chhetri et al (2021 observed G. chrysolopha in September and G. transversa in April in Sikkim, India. This moth's caterpillar is a major pest of Alnus nepalensis and Rhododendron arboreum in Kaski District and its outbreak usually occurs when there is low rainfall during post-winter months (Gurung et al 2021b). This moth has also been reported as a major pest of Quercus dilata in Azad State in Pakistan (Rahaman and Chaudhry, 1991) while Stebbing (1914) reported it as a serious pest of Quercus lamellose in Darjeeling District of India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A door-to-door survey method (presenting a questionnaire and brief interview) adopted to conduct this survey study [33]. To address the objectives of the study w selective sub-group from the large population was shortlisted from each city base their basic knowledge about the forest pests based on sampling size calculated by the mula (Equation (1)) [34] 𝑛𝑛 = 𝑁𝑁 1 + 𝑁𝑁(𝑒𝑒) 2 where n = sample size, N = total population (here N = 1,001,205 for QU, and N = 1,970 for PE), and e is the acceptable sample error (here e = 0.05). A total of 399 individuals that sub-group were randomly sampled in each city.…”
Section: Protocols Of Survey and Questionnaire Designmentioning
confidence: 99%
“…This is key to improving mountain rural areas' livelihood and sustainability (Mazzocchi & Sali, 2022). Timber and biomass for energy are also important ES supplied by mountains (e.g., Gurung et al, 2021) (Figure 1). In several areas is still one of the most important sources of local communities' income and is highly valued in the Alps (Gori et al, 2018), Carpathians (Melnykovych et al, 2018), Himalayas (Gentle & Marseni, 2012) and Africa -Burundi (Ndayizeye et al, 2020).…”
Section: Ecosystem Services Provisioningmentioning
confidence: 99%